EFEKTIVITAS MODEL PEMBELAJARAN THINK PAIR SHARE BERBANTUAN MEDIA FLIPBOOK INTERAKTIF TERHADAP PENINGKATAN PEMAHAMAN KONSEP IPAS SISWA SEKOLAH DASAR - Mega Satria, Anggita; Purbasari, Imaniar; Masfuah, Siti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low conceptual understanding of students at SD Negeri 1 Jojo, with an average score of 64.48 and indicator achievement of 45 percent. The study aims to determine the difference in mean scores and the improvement of IPAS conceptual understanding through the Think Pair Share learning model assisted by interactive Flipbook media, using a quantitative approach with a Pre Experimental One Group Pretest Posttest design on 18 third grade students. Data were collected through conceptual understanding tests, classroom observations, interviews, and documentation, and were analyzed using Paired Sample T Test and N Gain. The normality test showed values of 0.209 for the pretest and 0.151 for the posttest with significance greater than 0.05, indicating that the data were normally distributed. The Paired Sample T Test produced a significance value of 0.000 which is less than 0.05, meaning that H0 is rejected and H1 is accepted. The N Gain score for IPAS conceptual understanding was 0.8073, which falls into the high category, while the N Gain for process skills was 0.63, which falls into the medium category, indicating that the Think Pair Share model assisted by interactive Flipbook media is effective in improving students IPAS conceptual understanding. Keywords: Think Pair Share, Interactive Flipbook, Conceptual Understanding